Treatment Options and Outcomes of Penile Constriction Devices - Koifman, Leandro (Int Braz J Urol, 2019)
PURPOSE: To study the effect of penile constriction devices used on a large series of patients who presented at our emergency facility. We explored treatment options to prevent a wide range of vascular and mechanical injuries occurring due to penile entrapment. MATERIALS AND METHODS: Between January 2001 and March 2016, 26 patients with penile entrapment were admitted to our facility and prospectively evaluated. RESULTS: The time that elapsed from penile constrictor application to hospital admission varied from 10 hours to 6 weeks (mean: 22.8 hours). Non-metallic devices were used by 18 patients (66.6%) while the other nine (33.4%) had used metallic objects. Acute urinary retention was present in six (23%) patients, of whom four (66.6%) underwent percutaneous surgical cystotomy and two (33.4%) underwent simple bladder catheterization. The main reason for penile constrictor placement was erectile dysfunction, accounting for 15 (55.5%) cases. Autoerotic intention, psychiatric disorders, and sexual violence were responsible in five (18.5%), five (18.5%), and two (7.4%) cases, respectively. The mean hospital stay was 18 hours (range, 6 hours to 3 weeks). CONCLUSION: Penile strangulation treatment must be immediate through the extraction of the foreign body, avoiding vascular impairments that can lead to serious complications. Most patients present with low-grade injuries and use penile constrictors due to erectile dysfunction. Removal of constrictor device can be challenging. The use of specific tools for achieving penile release from constrictors is a fast, safe and effective method. Patients with urinary retention may require urinary diversion.